2015
DOI: 10.1371/journal.pone.0138515
|View full text |Cite|
|
Sign up to set email alerts
|

SALL4 as an Epithelial-Mesenchymal Transition and Drug Resistance Inducer through the Regulation of c-Myc in Endometrial Cancer

Abstract: SALL4 plays important roles in the development and progression of many cancers. However, the role and molecular mechanism of SALL4 in endometrial cancer remain elusive. In the present research, we have demonstrated that the expression of SALL4 was upregulated in endometrial cancer and correlated positively with tumor stage, metastases and poor survival of patients. The overexpression of SALL4 promoted the invasiveness in endometrial cancer cells, as indicated by the upregulation of mesenchymal cell marker N-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 41 publications
3
75
2
Order By: Relevance
“…It has been shown that using the dual PI3K/mTOR inhibitor NVP-BEZ235 inhibits the expression of c-MYC in pancreatic cancer cells (Sharma et al 2015). Moreover, c-MYC has also been linked to promoting EMT induction in endometrial cancer cells (Liu, et al 2015). Therefore, the decrease in c-MYC protein expression in the IRKD tumors in both the Rag/WT and Rag/MKR mice may contribute to the significantly decreased tumor sizes and reversal of EMT in the tumors of those mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that using the dual PI3K/mTOR inhibitor NVP-BEZ235 inhibits the expression of c-MYC in pancreatic cancer cells (Sharma et al 2015). Moreover, c-MYC has also been linked to promoting EMT induction in endometrial cancer cells (Liu, et al 2015). Therefore, the decrease in c-MYC protein expression in the IRKD tumors in both the Rag/WT and Rag/MKR mice may contribute to the significantly decreased tumor sizes and reversal of EMT in the tumors of those mice.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of its expression and epigenetic status have shown that SALL4 is de-regulated and aberrantly expressed in various cancers (Review in 64 ) such as leukemia 65 , germ cell tumors 6667 , hepatocellular carcinoma (HCC) 2468 , gastric cancer 20,6973 , colorectal carcinoma 7476 , esophageal squamous cell carcinoma 77,78 , breast cancer 7981 , endometrial cancer 82,83 , lung cancer 8486 and glioma 87 . Functionally, SALL4 is important for the survival 38,80,82,8893 , drug resistance 82,94 and metastasis 69,82 of many of these cancer cells (Figure 4).…”
Section: Sall4 In Cancersmentioning
confidence: 99%
“…Finally, SALL4 can regulate the expression of cell surface molecules such as EpCAM 91,113 , epithelial-mesenchymal transition (EMT) related factors (e.g. SNAI1 113 , CXCR4, TWIST1 91 , E-Cadherin 69,83,142 , VIM, and ZEB1 143 ) in cancers (Figure 5). …”
Section: Molecular Dissection Of Sall4 Functions In Cellsmentioning
confidence: 99%
“…In addition to hematopoietic malignancies, SALL4 is also found to be upregulated in solid tumours including liver cancer, 13, 14 colon cancer, 15, 16 breast cancer, 17, 18 endometrial cancer, 19, 20 lung cancer 21, 22 and glioma. 23 The recent studies also suggest an oncogenic role of SALL4 in solid tumours.…”
Section: Introductionmentioning
confidence: 99%